Targeting Angiogenesis With Peptide Vaccines - Rahat, Michal A. (Frontiers in Immunology, 2019)
Most cancer peptide vaccinations tested so far are capable of eliciting a strong immune response, but demonstrate poor clinical benefits. Since peptide vaccination is safe and well tolerated, and several indications suggest that it has clear potential advantages over other modalities of treatment, it is important to investigate the reasons for these clinical failures. In this review, the current state of the art in targeting angiogenic proteins via peptide vaccines is presented, and the underlying reasons for both the successes and the failures are analyzed. The review highlights a number of areas critical for future success, including choice of target antigens, types of peptides used, delivery methods and use of proper adjuvants, and suggests ways to achieve better clinical results in the future.